2019
DOI: 10.1111/apm.13006
|View full text |Cite
|
Sign up to set email alerts
|

spoT‐mediated stringent response influences environmental and nutritional stress tolerance, biofilm formation and antimicrobial resistance in Klebsiella pneumoniae

Abstract: Klebsiella pneumoniae is an important opportunistic pathogen with significant potential for virulence and multidrug resistance. Treatment failure often occurs because the pathogen may couple virulence and drug resistance with the stringent response. This study assessed the role of the spoT gene in environmental and nutritional stress tolerance, exopolysaccharide capsule production and biofilm formation. spoT mutants were constructed using the lambda red recombinase technique, and mutant and wild‐type (WT) stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The gene encoding SpoT, an enzyme that contributes to regulation of stress responses (including the stringent response) in K. pneumoniae , was upregulated during culture in NHS, but it was not changed significantly by exposure to mupirocin under our assay conditions ( Fig. 3B ) ( 38 ). It is possible that the stringent response was induced by mupirocin in these ST258 isolates, but our ability to detect changes in gene expression was limited technically.…”
Section: Discussionmentioning
confidence: 86%
“…The gene encoding SpoT, an enzyme that contributes to regulation of stress responses (including the stringent response) in K. pneumoniae , was upregulated during culture in NHS, but it was not changed significantly by exposure to mupirocin under our assay conditions ( Fig. 3B ) ( 38 ). It is possible that the stringent response was induced by mupirocin in these ST258 isolates, but our ability to detect changes in gene expression was limited technically.…”
Section: Discussionmentioning
confidence: 86%
“…This gene, which encodes the bifunctional (p)ppGpp synthase/hydrolase, has been associated with obtaining maximum protection against stress (nutrient starvation, heat shocks, presence of NaCl and/or ethanol, etc.) and, therefore, facilitating bacterial pathogeny and dissemination [ 124 , 125 ]. Moreover, some authors have related it with the expression of various EPS operons (i.e., vps , pea , peb , bcs ) in diverse bacterial genera, such as Vibrio , Xanthomonas and Pseudomonas ; and, in consequence, with biofilm matrix production [ 26 , 61 , 122 , 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Li et al reported that low concentrations of antibiotics could induce the formation of persister cells, and K. pneumoniae produces high levels of tolerant persister cells to survive high concentrations of bactericidal antibiotics (Li et al, 2018). Amino acid starvation could increase the biofilm survival percent of K. pneumoniae strains treated with ceftazidime from 22-41% to 70 to 388% (Davis and Brown, 2020). Thus, the bacteria in the persistent state could tolerate the nutrient limitation and stress conditions in the biofilms and increase bacterial antibiotic resistance.…”
Section: Biofilm and Its Association With Antibiotic Resistancementioning
confidence: 99%